FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS TENAGA KERJA BURUH PANEN KELAPA SAWIT DI PT. PATRI AGUNG PERDANA ESTATE RAMBUTAN DESA SUKA PINDAH KABUPATEN BANYUASIN - Billa, Manova Tasya; Iswarini, Harniatun (Universitas Muhammadiyah Palembang, 2021)
This study was conducted to determine the effect of harvester age, length of formal education, number of dependents, wages and premiums and to find out how much labor productivity of oil palm harvesters is at PT Patri Agung Perdana Estate Rambutan, Suka Moving Village, Rambutan District, Banyuasin Regency. This research was conducted in Suka Moving Village, Rambutan District, Banyuasin Regency from February to March 2021. The research method used was a survey method. The sampling method used is saturated sampling. To answer the first problem, it was analyzed by multiple linear regression using the SPSS statistics 25 computer application program. Furthermore, to answer the second problem, the productivity formula was used. The results of the statistical test showed that wages and premiums had a significant effect on the productivity of oil palm harvesters at PT Patri Agung Perdana Estate Rambutan. Meanwhile, age, length of education and number of dependents did not significantly affect the productivity of oil palm harvesters at PT Patri Agung Perdana Estate Rambutan. The length of formal education did not significantly affect the productivity of oil palm harvesters at PT Patri Agung Perdana Estate Rambutan. It is known that the FFB Production Value/month is 38,496 Kg/month with 25 working days, so the productivity level of harvesters per day is 1,539 Kg/HK.